Hatching success and nesting depth of Chelonia mydas (family: cheloniidae) in eggs relocation programme at Penang Island, Peninsular Malaysia - Sarahaizad, M.S.; Shahrul-Anuar, M.S. (Penerbit Universiti Kebangsaan Malaysia, 2014)
A study on hatching success and nesting depth of Chelonia mydas was conducted at Penang Island, Peninsular Malaysia from 1 December 2009 to 31 December 2010. Twenty nine natural nests were relocated for ex situ incubation, and incubated at 55, 65, and 75 cm depth. Two hatcheries plots, one covered (Hatchery A) and another one uncovered (Hatchery B), were prepared. This study found that nest temperature influenced the hatching success, incubation period, and hatchling sizes. High hatching success and less days of incubation period were found in Hatchery B as the plot was uncovered and exposed to sunlight, thus had higher temperature than covered Hatchery A. The mean nest temperature in Hatchery A was 28.0°C, which was lower than Hatchery B, 29.5°C. There was a significant difference in nest temperature at 55, 65, and 75 cm nesting depths in both plots (p<0.01). As the nesting depth increased, the nest temperature also increased. The mean hatching success was 50.5% in Hatchery A and 59.8% in Hatchery B. The mean incubation period was 54.9 days in Hatchery A and 50.7 days in Hatchery B. There was a linear relationship between nesting depth and hatching success, p<0.01. Due to warmer temperature, Hatchery B produced hatchlings with bigger sizes. In conclusion, nest temperature does affect the hatching success (p<0.01) and morphological characteristics of hatchlings (p<0.01). Eggs should be incubated in an uncovered plot with nesting depth of 55 cm for a maximum hatching success.